A Region on Chromosome 7 Related to Differentiation of Rice (Oryza sativa L.) Between Lowland and Upland Ecotypes - Md. Nashir Uddin; Yoshimichi Fukuta (Frontiers in Plant Science, 2020)
Due to global population expansion and climate change impacts, the development of a stable yielding variety that adapts well to unfavorable conditions for rice cultivation, can contribute to sustainable and stable production in rice (Oryza sativa L.). Understanding genetic differentiations to ecotypes for rice cultivations, such as upland, rainfed lowland, and irrigated lowland, is very important to develop the breeding materials for adapting to each environmental condition. The upland landrace variety basically has low tiller/panicle numbers and a large panicle, and the plant architecture is different from that of the lowland variety. The tiller and panicle numbers have been considered as one of the most difficult traits for genetic changes artificially in rice breeding. A low tiller recessive gene ltn2 originated from a New Plant Type variety, IR 65600-87-2-23, harboring segments from an upland variety, Ketan Lumbu (Tropical Japonica Group), was found on chromosome 7, and the other QTLs for culm length, culm weight, panicle length, panicle weight, seed fertility, harvest index, and soil surface rooting were also detected in the same chromosome region. These low tiller genes and the other QTLs were estimated to play an important role in developing the architecture for upland rice. Some QTLs for root growth angle, DRO3 and qSFR7, were also found in the same chromosome region from upland varieties categorized into the Tropical Japonica Group, and the QTLs may also be relevant to upland adaptation together with other traits. Previous studies using high throughput re-sequencing (whole genome variation data) of a large batch of rice accessions could identify the ecotype differentiated genomic regions (EDRs) and Ecotype differentiated genes (EDGs) such as Os07g0449700, a type response regulator, which is critical in upland adaptation in the same region of chromosome 7. Two selective loci, E3735 and E4208, for upland and lowland differentiation, and their corresponding genes Os07g0260000 and Os07g0546500 were also detected on chromosome 7 by drought-responding EST-SSRs. These findings indicate that the region on chromosome 7 is highly possible to related to the plant shoot and root architecture in the upland rice variety that has an important role and differentiates between upland and lowland ecotypes.